Superstition In Mark Twain's Adventures Of Huckleberry Finn (1884) - Amrina, Nur Wahidah Ullya (2016)
ABSTRACT This study is about Superstitions in Mark Twain's Adventures of Huckleberry Finn (1884) which is analyzed by using Sociological approach. The objectives of the study are to know the types of superstition, to know how superstition directed in the novel, and to know the reason why Mark Twain addressed Superstition in Adventures of Huckleberry Finn novel based on Sociological approach. This research belongs to qualitative research. The primary data of this research is Adventures of Huckleberry Finn novel by Mark Twain in 1884, while the secondary data of this research are other sources related to the study, such as: website, dictionary and some books which support this research. The researcher draws three conclusions in this research. Firstly, of the six types of superstition, there are only three types are found in the novel. The three types are daily life, death-ghost-demons, and animal-plants. Secondly, the superstition is directed in the novel through the characters, setting, events, and style. Third is the underlying reason why Mark Twain address superstition in his novel is to help the story progress and just a joke to entertain the reader. Keywords: Superstition, Adventures of Huckleberry Finn, Sociological Approach.